Utilization of Law Against Conflicting Public Policies - Bakri, Riani; Jeddawi, Murtir; Husain, Muh. Fachril; Utami, Fadilah Risqi (Institut Pemerintahan Dalam Negeri Kampus Sulawesi Selatan, 2025)
Good and qualified public policies can be sued, let alone public policies that actually cause harm to the community. This paper aims to analyze public policies (legislation) that conflict with each other, even though the public policies (legislation) in question have not been revoked. This paper uses a library research method by identifying relevant literature sources, including books, academic journals, and policy documents that discuss the relationship between law and public policy. Analysis is carried out on the sources that have been collected to understand how law can function as a tool to resolve conflicts in public policy. The results of the study indicate that Indonesia as a country of law based on Article 1 paragraph (3) of the 1945 Constitution, every government action by the government is always based on (written) law and norms that apply at a certain time and place. However, in the implementation of the government as an implication of the written legal regulation regime, sometimes there is a conflict between one legal regulation and another, either lower legal regulations against higher legal regulations or between equal legal regulations, to overcome the lack of legal basis for public service, the application of the principle of derogation becomes a legal instrument to provide legal certainty.